Banking Support in Economic Sector Affected by Covid-19 To Support Acceleration of Economic Growth and Overcome the Long-Term Impact - Renta Yustie; Novi Theresia Kiak (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2023)
Indonesia's economic growth contracted 0.7% because it was influenced by the Covid-19 pandemic, this study examines the potential and contribution of banks in improving Indonesia's economic conditions during the pandemic. The banking sector is one sector that greatly influences the rate of economic growth of a country and banking has great potential to develop more rapidly in Indonesia. This study uses quantitative methods and uses panel data with a sample of 18 business sectors in Indonesia with a time span of 2018 to 2021. The variables in this study are GDP, Loan Interest Rates and Commercial Bank Loans with this calculation using the EViews 9 analysis tool by testing hypothesis and classical assumption test, it is hoped that the variables used in the study support banking in the economic sector affected by COVID-19 and have an insignificant effect and have a positive relationship in supporting the acceleration of economic growth and overcoming the prolonged impact.